Gamma Irradiation of Brown Rice: Effects of Dose, Variety, Paddy Age, and Packaging on Fungal Control, Shelf-Life and Post-Harvest Cost Estimate - G.B. Abrera; G. Diano; M.M. Tolentino; M.C.B. Gragasin; M.L.C. Cobar; G. Caraos; Z.M. De Guzman; H.M. Solomon; C.O. Asaad; C.C. Deocaris (Journal of Food Quality and Hazards Control)
Background: Brown rice offers superior nutritional value compared to polished white rice but is less favored in rice-consuming countries due to its limited shelf-life. This study evaluates the efficacy of gamma irradiation in reducing fungal contamination in brown rice and extending its shelf-life, considering factors such as paddy age, rice variety, and packaging type. Methods: The efficacy of gamma irradiation (0-1 kGy) in reducing fungal contamination in brown rice was evaluated. RC-160 and SL-7 rice varieties (240 kg per variety) were harvested from Central Luzon (Region III) during the dry season (March–April 2023). One kg of two and eight-week-old paddy grains were packed in either Super Bag™, an International Rice Research Institute developed hermetic packaging, or conventional Polyethylene bags. Mold and Yeast Counts were quantified using 3M Petrifilm™ following Association of Official Agricultural Chemists official methods. Fifty g of each sample were homogenized in Butterfield’s phosphate buffer, serially diluted, plated, and incubated at 25±1 °C for 3-5 days. Statistical analyses were performed using one-way ANOVA and Tukey’s HSD post-hoc test with Statistical Tool for Agricultural Research (STAR) software, version 2.0.1 (IRRI). Results: Gamma irradiation at one kGy significantly (p<0.05) reduced Mold and Yeast Counts, with effects sustained for up to eight months. Paddy age and packaging type had no significant influence on fungal load. A dose of 0.58 kGy achieved a 1-log (90%) reduction in Aspergillus niger, while 3 kGy achieved complete inactivation, extending shelf-life up to six months. Cost analysis showed irradiation, logistics, and added storage fees increased retail price per kg by 0.14, 0.04, and US$0.02, respectively. Conclusions: Gamma irradiation effectively controls fungal contamination and extends brown rice shelf-life, potentially enhancing consumer confidence and promoting wider adoption of brown rice.